2013
DOI: 10.1177/1477153513509258
|View full text |Cite
|
Sign up to set email alerts
|

Daylight and health: A review of the evidence and consequences for the built environment

Abstract: Daylight has been associated with multiple health advantages. Some of these claims are associations, hypotheses or beliefs. This review presents an overview of a scientific literature search on the proven effects of daylight exposure on human health. Studies were identified with a search strategy across two main databases. Additionally, a search was performed based on specific health effects. The results are diverse and either physiological or psychological. A rather limited statistically significant and well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(122 citation statements)
references
References 66 publications
5
112
2
3
Order By: Relevance
“…Borisuit et al 33 and Münch et al 34 mentioned the importance of daylight availability for occupant's work satisfaction and alertness during the day. This unanimous agreement in the importance of daylight is in accordance to Galasiu and Veitch 19 as well as Aries et al 22 .…”
Section: (In)consistenciessupporting
confidence: 63%
See 1 more Smart Citation
“…Borisuit et al 33 and Münch et al 34 mentioned the importance of daylight availability for occupant's work satisfaction and alertness during the day. This unanimous agreement in the importance of daylight is in accordance to Galasiu and Veitch 19 as well as Aries et al 22 .…”
Section: (In)consistenciessupporting
confidence: 63%
“…Light with shorter wavelengths could trigger the greatest ipRGc response 2 and since daylight is rich in this bluish part of the spectrum, this may explain why individuals prefer daylight during the day. In 2013, Aries et al 22 presented an overview of all proven effects of daylight exposure on human health and reported rather limited scientific evidence of the association between daylight and its health consequences. They recommended further research to focus on the nature of why some individuals prefer daylight and others do not, how the dose-response curves for alertness, performance and mood should be interpreted, and the effect of daylight on human health in the general population.…”
Section: Light Sourcesmentioning
confidence: 99%
“…Light, defined as electromagnetic radiation to which the human retina is sensitive [1], has been studied as part of architectural environments to provide visual comfort and to improve human mood and alertness [2][3][4][5][6][7]. Today, there is an effort to differentiate "visual lighting levels" from "biological lighting levels" [8], and a need to understand human physiological and behavioral responses to electromagnetic radiation [9][10][11][12], because light entering the eye does not only serve vision, but also our circadian system [13][14][15]. Light affects our circadian timing [16][17][18][19][20], alertness [21,22], core body temperature [22], heart rate [22][23][24], cortisol production [25], and objective alertness [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…While lighting is estimated to represent roughly 40% of total electric usage in office buildings, it has been reported that daylight harvesting can lead to 20-77% savings in the lighting consumption of buildings [6,7]. Daylight availability inside buildings can also have multiple health advantages for building users, such as decreasing fatigue, relieving seasonal affective disorder, and diminishing depressive symptoms [8]. Access to daylight can provide information about time and weather, as well as reducing feelings of isolation, stress, and claustrophobia [9,10].…”
Section: Introductionmentioning
confidence: 99%